Scrub typhus seroprevalence from an eastern state of India: findings from the state-wide serosurvey. (10th August 2022) - Parai, Debaprasad; Pattnaik, Matrujyoti; Kshatri, Jaya Singh; Rout, Usha Kiran; Peter, Annalisha; Nanda, Rashmi Ranjan; Sahoo, Subrat Kumar; Mansingh, Asit; Choudhary, Hari Ram; Dash, Girish Chandra; Praharaj, Ira; Bhattacharya, Debdutta; et al.
Abstract: Background: Scrub typhus is a mite-borne infectious disease caused primarily by the obligate intracellular bacteria Orientia tsutsugamushi, which is transmitted by chigger mites. The objective of this study was to determine the prevalence of scrub typhus among adults in Odisha, an eastern state of India. Methods: A descriptive cross-sectional study was conducted to analyse 1840 serum samples from five districts (Khordha, Cuttack, Ganjam, Malkangiri and Sundargarh) of Odisha collected during 2020–2021. Both immunoglobulin G (IgG) and IgM antibodies against scrub typhus were tested using commercial enzyme-linked immunosorbent assay kits. Point estimates of the 95% confidence interval and adjusted odds ratio were calculated. Results: Of 1840 participants, the prevalence of IgG positivity was 1034 (56.19%) and that of IgM was 523 (28.42%). The majority of participants were in the 18–45 y age group (53.7%). Cuttack had the highest IgG positivity (64.54%) and Malkangiri had the lowest (29.32%). The highest and lowest positivity for IgM were found in Malkangiri (40.84%) and Cuttack (25.30%), respectively. Conclusions: With an increasing number of infections detected in the state, scrub typhus is emerging as a public health threat. Increasing awareness among the general public and healthcare professionals through health education campaigns regarding scrub typhus is essential. Early detection of the disease through the establishment of a laboratory surveillance system is required to control the transmission of scrub typhus.